FGFR2-CCDC6 fusion gene promotes the proliferation of Hucct-1 cells: FGFR2-CCDC6 gene promotes the Hucct-1 cells - Wang, Xianyan; Li, Hongmei; Zhang, Ning; Wu, Tian; Wang, Shaoqing (Cellular and Molecular Biology, 2022)
To investigate the effect of the FGFR2-CCDC6 fusion gene on cell proliferation and its mechanism of action, pCDNA3.1- FGFR2bWT, pCDNA3.1- FGFR2-CCDC6 expression plasmids were transiently transfected into Hucct-1 cells using Lipo-2000 liposomes. The effect of the fusion gene on cell proliferation was examined by MTT and the expression of FGFR2/AKT/signaling pathway proteins was detected by Western blot. Results showed that Hucct-1 cells transfected with the FGFR2-CCDC6 fusion gene showed increased FGFR2 protein expression (P<0.001) and significantly higher cell proliferation capacity (P<0.001) compared to normal controls. It was concluded that The FGFR2-CCDC6 fusion gene excessively activates the AKT, and ERK signaling pathway downstream of FGFR2 and plays a role in promoting cell proliferation.